Thermal Resistance of Certain Oncogenic Viruses Suspended in Milk and Milk Products - Sullivan, Robert (1971)
Thermal destruction rate curves were determined for adenovirus 12, reovirus 1, and herpes simplex virus in sterile milk, raw milk, raw chocolate milk, and raw ice cream mix. At 40 to 60 C, the curves were asymptotic to the base line. At 65 C, which is near the pasteurization standard, the curves approached a first-order reaction. Thermal resistance studies, by means of in vivo assays, of Moloney and Rauscher leukemia viruses and Moloney and Rous sarcoma viruses indicated that Rous sarcoma was the most resistant. A comparison of the 12D processes of Rous sarcoma virus, reovirus 1, adenovirus 12, and herpes simplex virus in ice cream mix (the most protective of the suspending menstrua studied) with the U.S. Public Health Service pasteurization standard indicated an adequate safety factor in current pasteurization practices.